Participatory Action Research for Learning Chemistry: A Case of Public Schools in Nepal - Acharya, Kamal Prasad (Journal of Advanced College of Engineering and Management, 2019)
The present study reconnoiters the application of participatory action research (PAR) in improving the performance of students in chemistry sections. A mixed method research is employed focusing PAR as qualitative and experimental as a quantitative with equivalent groups. Two schools were purposively selected (one leader and one leader) in Chitwan and Nawalparasi districts. All the students in the leader school are given intervention. Thirty students from the feeder school are in control group. Intervention was done by laboratory activities in chemistry teaching. PAR approach is used in the leader school during intervention. Pre-test and post-test were used to collect the data. Data are analyzed using inferential statistics: independent student t-test and analysis of covariance (ANCOVA). The result shows that the experimental group outperformed to control group suggesting that PAR approach enhanced performance of lower and high achievers more than the lecture method of teaching.